2020
DOI: 10.1016/j.cortex.2020.01.021
|View full text |Cite
|
Sign up to set email alerts
|

No strong evidence that social network index is associated with gray matter volume from a data-driven investigation

Abstract: Recent studies in adult humans have reported correlations between individual differences in people's Social Network Index (SNI) and gray matter volume (GMV) across multiple regions of the brain. However, the cortical and subcortical loci identified are inconsistent across studies. These discrepancies might arise because different regions of interest were hypothesized and tested in different studies without controlling for multiple comparisons, and/or from insufficiently large sample sizes to fully protect agai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Although the aforementioned studies used different social network indicators and measured the indicators for different periods of time, ranging from 1 week to 1 month, and from an individual egocentric network to a sociocentric network, they reported relatively reproducible findings. However, Lin et al (2019) repeated previous studies and did not identify a brain structure that was significantly related to social network structure. The authors postulated that the relationship between dynamic indicators of social network structure and brain function, instead of brain structure, should be emphasized because social networks are dynamic, as social relations might naturally increase or decrease over time, but the brain structure is relatively stable (Lin et al, 2019).…”
Section: Other Brain Regionsmentioning
confidence: 77%
See 1 more Smart Citation
“…Although the aforementioned studies used different social network indicators and measured the indicators for different periods of time, ranging from 1 week to 1 month, and from an individual egocentric network to a sociocentric network, they reported relatively reproducible findings. However, Lin et al (2019) repeated previous studies and did not identify a brain structure that was significantly related to social network structure. The authors postulated that the relationship between dynamic indicators of social network structure and brain function, instead of brain structure, should be emphasized because social networks are dynamic, as social relations might naturally increase or decrease over time, but the brain structure is relatively stable (Lin et al, 2019).…”
Section: Other Brain Regionsmentioning
confidence: 77%
“…However, Lin et al (2019) repeated previous studies and did not identify a brain structure that was significantly related to social network structure. The authors postulated that the relationship between dynamic indicators of social network structure and brain function, instead of brain structure, should be emphasized because social networks are dynamic, as social relations might naturally increase or decrease over time, but the brain structure is relatively stable (Lin et al, 2019). Although many of the studies described above have discussed the functions of brain regions, they only focused on resting-state networks, and few of them mention how social networks affect the processing of social information by the brain.…”
Section: Other Brain Regionsmentioning
confidence: 77%
“…Second, the range of social connections included in the present study was not the same as in social network indices of previous studies (Lin et al, 2020). Specifically, we measured the size of the social network by the number of reply and follow/followers on Twitter, which includes both real-world friends and non-friends (unlike Facebook friends; see Kanai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While these findings are consistent with animal studies showing an association between social isolation and hippocampal neurogenesis [57], it is also conceivable that the expedition-related changes are a byproduct of sensory deprivation. Previous studies also observed that larger and more diverse social networks positively correlate with amygdala volume [58], but a recent study failed to replicate this association [59]. Along these lines, a rare patient with bilateral amygdala damage showed a normal size and complexity of her social network [60], indicating that an intact amygdala is not necessary to maintain social relationships or at least can be compensated for [61].…”
Section: Brain Structural Adaptations Associated With Lonelinessmentioning
confidence: 94%